A longitudinal examination of the effect of physical exercise on the emotional states of college students: exploring the sense of coherence as a mediator through a cross-lagged panel analysis - Cao, Yunxia; Luo, Lin (Frontiers in Behavioral Neuroscience, 2024)
longitudinal study aimed to investigate the causal relationship between physical exercise and emotional states among university students, focusing on the mediating role of sense of coherence.Method ： A total of 1215 university students (aged 18-25 years) were recruited and completed questionnaires assessing physical activity (International Physical Activity Questionnaire-Short Form), emotional states (Positive and Negative Affect Schedule), and sense of coherence (Sense of Coherence Scale-13) at three time points over a three-month period. Preliminary analyses included independent samples t-tests, chi-square tests, and Pearson correlations. Cross-lagged panel mediation analysis was conducted using Mplus 8.3, with bootstrapping employed to test indirect effects.Results： Results indicated that sense of coherence significantly predicted positive affect ( β = 0.259-0.369, p < 0.001). Positive affect, in turn, predicted physical exercise ( β = 0.083-0.182, p < 0.05), while negative affect also influenced physical exercise (β = -0.096-0.203, p < 0.05). Physical exercise indirectly influenced positive affect through sense of coherence (β = 0.037, p = 0.045), and positive affect indirectly influenced physical exercise through sense of coherence (β = 0.029, p = 0.028). Other indirect effects involving physical exercise, sense of coherence, and negative affect were non-significant.Conclusion： This study underscores the importance of sense of coherence in promoting emotional well-being among university students and in the reciprocal relationship between physical exercise and positive emotional states. Findings suggest that interventions targeting sense of coherence may enhance the emotional benefits of physical exercise. Future research should explore other potential mediators and moderators of the relationship between physical exercise and emotions and examine the effectiveness of sense of coherence-based interventions on well-being in this population.